Multibody dynamic modeling and analysis of cable-driven snake robot considering clearance and friction based on ALE method. (June 2023) - You, Pu; Liu, Zhuyong; Ma, Ziqi
Highlights: Cable-hole clearance is efficiently modeled using arbitrary Lagrangian Eulerian method. Cable-hole clearance has a great influence on the motion accuracy of cable-driven manipulators. Clearance and friction can induce cable slack phenomenon. Abstract: Cable-driven snake robot (CDSR) is a kind of slender manipulator with excellent maneuverability, which is widely applied in complex spaces. However, several nonlinear factors, such as clearance and contact between cable and hole, can lead to uncertainty of motion and danger of cable under extreme tension, which can affect the performance of the CDSR. In this paper, a multibody dynamic model of CDSR considering both friction and clearance is proposed. The arbitrary Lagrangian Eulerian (ALE) method is used to model the driving cable. The ALE node is constrained in the hole plane and the contact forces are evaluated using nonlinear impact function to describe the cable-hole interaction. Moreover, contact force regularization is adopted to facilitate convergence. A numerical test demonstrates that the clearance model can describe the contact behavior of cable and hole accurately. Moreover, the effect of clearance sizes on CDSR are studied. It shows that the manipulation precision can be dramatically reduced due to the increase of clearance size. Finally, the driving cable slack phenomenon induced by the coupling effect of clearance and friction is revealed. The presented work is expected to be applied for the compensation of feedback control and tension optimization design of CDSR.